1998
DOI: 10.1093/humrep/13.7.1796
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance in idiopathic premature ovarian failure: analysis of 71 cases

Abstract: Premature ovarian failure is defined as cessation of ovarian function under the age of 40 years and affects approximately 1% of women in the general population. The aetiology of this disorder is still unknown in most cases. Although there have been some reports of familial premature ovarian failure, very little is known about the incidence and inheritance pattern of its idiopathic form. The aims of this study were to investigate the incidence and inheritance pattern of familial premature ovarian failure in a h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
78
0
4

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 152 publications
(89 citation statements)
references
References 24 publications
7
78
0
4
Order By: Relevance
“…A GWAS database has already begun to emerge for POI cases [10]. POI has proven to be largely familial [21,22]. As we have shown here, evidence supports that pathologic DOR behaves in a similar fashion.…”
Section: Future Directionssupporting
confidence: 74%
See 1 more Smart Citation
“…A GWAS database has already begun to emerge for POI cases [10]. POI has proven to be largely familial [21,22]. As we have shown here, evidence supports that pathologic DOR behaves in a similar fashion.…”
Section: Future Directionssupporting
confidence: 74%
“…For example, a study examining 71 chromosomally normal patients characterized as idiopathic POI found 31 % of cases to be familial, exemplifying the large genetic basis of POI [22]. The purpose of this review is to identify the genes that may be associated with pathologic DOR, including those found in humans, as well as candidate genes found in mice, to achieve the goal of ultimately developing a genetic screening panel for pathologic DOR prior to initiating an IVF cycle.…”
Section: Introductionmentioning
confidence: 99%
“…Although epidemiological evidence based on mother-daughter pairs supports the heritability of menopausal age [95,96] and some Authors reported cases of familial premature menopause [97,98], very little is known about the inheritance pattern of the idiopathic POF. The overall incidence of familial POF ranges between 4% and 31% depending on the inclusion criteria adopted and the availability of a detailed family history [95,96,98].…”
Section: Genetics Of Familial Idiopathic Pofmentioning
confidence: 99%
“…The overall incidence of familial POF ranges between 4% and 31% depending on the inclusion criteria adopted and the availability of a detailed family history [95,96,98]. However, due to rare familial cases with full pedigrees, few genome-wide linkage analyses have been performed so far.…”
Section: Genetics Of Familial Idiopathic Pofmentioning
confidence: 99%
See 1 more Smart Citation